2021
DOI: 10.1177/15269248211046037
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Valganciclovir Prophylaxis Is Safe and Cost-Saving in CMV-Seropositive Kidney Transplant Recipients

Abstract: Introduction: Observational studies suggest that low-dose valganciclovir prophylaxis (450 mg daily for normal renal function) is as effective as and perhaps safer than standard-dose valganciclovir (900 mg daily) in preventing CMV infection among kidney transplant recipients. However, this practice is not supported by current guidelines due to concerns for breakthrough infection from resistant CMV, mainly in high-risk CMV donor-seropositive/recipient-seronegative kidney transplant recipients. Standard-dose valg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Dose adjustments have been proposed to ascertain efficacy, while limiting the potential toxicities associated with higher VCG concentrations, namely, its effect on the bone marrow and associated cytopenias. A lower VGC dosing (450 mg daily for an eGFR ≥60 mL/min/m 2 ) has been shown to significantly reduce the incidence of leucopenia and to be cost-effective [ 21 , 22 ]. For this study, we followed the proposed dose adjustments as shown in the Compendium ® , an open-access Swiss medication database operated by HCI Solutions SA and regularly updated, which provides short monographs, clear clinical decision support and interaction profiles, and dose adjustments based on renal function of the drugs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dose adjustments have been proposed to ascertain efficacy, while limiting the potential toxicities associated with higher VCG concentrations, namely, its effect on the bone marrow and associated cytopenias. A lower VGC dosing (450 mg daily for an eGFR ≥60 mL/min/m 2 ) has been shown to significantly reduce the incidence of leucopenia and to be cost-effective [ 21 , 22 ]. For this study, we followed the proposed dose adjustments as shown in the Compendium ® , an open-access Swiss medication database operated by HCI Solutions SA and regularly updated, which provides short monographs, clear clinical decision support and interaction profiles, and dose adjustments based on renal function of the drugs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, ganciclovir-resistant CMV was observed in the reduced-dose group (2 vs 0 patients) [ 34 ]. A study comparing valganciclovir 450 mg daily to 900 mg daily in 179 intermediate-risk KTRs found no difference in rates of CMV reactivation (0% vs 3.4%, respectively, P = .179) or neutropenia [ 35 ]. A study of 90 high-risk SOT recipients observed a lower incidence of leukopenia with reduced-dose valganciclovir (44% vs 75%, P < .01), but with a numerically higher rate of CMV breakthrough infection (13.3% vs 2.2%, P = .11) [ 36 ].…”
Section: Myth 3: (Val)ganciclovir Dosing Is Based On Drug Concentrati...mentioning
confidence: 99%